Genetic composition of replication competent clonal HIV-1 variants isolated from peripheral blood mononuclear cells (PBMC), HIV-1 proviral DNA from PBMC and HIV-1 RNA in serum in the course of HIV-1 infection. - Edo-Matas, D; van Gils, M; Bowles, E; Navis, M; Rachinger, A; Boeser-Nunnink, B; Stewart-Jones, G; Kootstra, N; van 't Wout, AB; Schuitemaker, H (2010)
The HIV-1 quasispecies in peripheral blood mononuclear cells (PBMC) is considered to be a mix of actively replicating, latent, and archived viruses and may be genetically distinct from HIV-1 variants in plasma that are considered to be recently produced. Here we analyzed the genetic relationship between gp160 env sequences from replication competent clonal HIV-1 variants that were isolated from PBMC and from contemporaneous HIV-1 RNA in serum and HIV-1 proviral DNA in PBMC of four longitudinally studied therapy naïve HIV-1 infected individuals. Replication competent clonal HIV-1 variants, HIV-1 RNA from serum, and HIV-1 proviral DNA from PBMC formed a single virus population at most time points analyzed. However, an under-representation in serum of HIV-1 sequences with predicted CXCR4 usage was sometimes observed implying that the analysis of viral sequences from different sources may provide a more complete assessment of the viral quasispecies in peripheral blood in vivo.